Revealing the role of crystal orientation of protective layers for stable zinc anode - Qi Zhang (Nature Portfolio, 2020)
Zinc affinity plays a key role in the zinc plating and stripping processes but its internal mechanism is still unclear. Here, the authors report a protective layer with controllable zinc affinity by adjusting the crystal orientation to suppress the dendrite growth on the zinc anode interface.